Early Pregnancy Maternal Serum PAPP-A and Urinary Protein-Creatinine Ratio as Predictive Markers of Pregnancy Induced Hypertension - Nasrin, B; Fatema, N; Jebunnessa, F; Shamim, S; Chowdhury, SB; Ali, L (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):267-74. The abstract of this article is available on the PubMed website